Decay properties of 2.05-h 95245Am. (March 2019) - Ahmad, I.; Kondev, F.G.
Abstract: Gamma rays following the β − decay of the 245 Am radionuclide ( T 1 / 2  = 2.05 h) were measured in early 1970s with a co-axial Ge(Li) detector using a chemically and isotopically pure, mass-separated 245 Am source. These data were analyzed in the present work where several weak γ rays in 245 Cm were identified. The 245 Am decay scheme was deduced and extended when compared to the previously known one. Highlights: Gamma rays following β − decay of the 245 Am radionuclide were measured with a 25-cm 3 Ge(Li) spectrometer and a mass-separated 245 Am source. Our results provide more accurate values for the gamma-ray energies and intensities for the observed transitions and extend the previously known 245 Am β − -decay scheme. Gamma-ray studies using a mass-separated 245 Am source.